2020
DOI: 10.3390/w12020315
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment Methodology for Urban Residential Rainwater Tank Implementation

Abstract: Rainwater tanks are increasingly being implemented as part of the integrated urban water management paradigm where all sources of water, including potable, stormwater and recycled, are considered eligible to contribute to the urban water supply. Over the last decade or so, there has been a rapid uptake of rainwater tank systems in urban areas, especially in Australian cities, encouraged through financial incentives, but more importantly, from change in residential building codes effectively mandating the insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…These results are not different from findings of research conducted in Australia, where it is common to use rainwater in urban households for drinking and cooking purposes, sometimes without disinfection treatment (Gardner & Vieritz 2010). Over the 6 years to 2013, home rainwater increased from 15 to 28% in Australia (Sharma & Gardner 2020).…”
Section: Sources Of Water Used Among In Haiti and The Perceptions Of The Usersmentioning
confidence: 50%
“…These results are not different from findings of research conducted in Australia, where it is common to use rainwater in urban households for drinking and cooking purposes, sometimes without disinfection treatment (Gardner & Vieritz 2010). Over the 6 years to 2013, home rainwater increased from 15 to 28% in Australia (Sharma & Gardner 2020).…”
Section: Sources Of Water Used Among In Haiti and The Perceptions Of The Usersmentioning
confidence: 50%
“…Scholars in the built environment field have not yet explored the factors in implementation studies, which has affected the definitive source for RWH implementation research. The implementation of RWH is generally poor and this has to be addressed to benefit the environment at large [14,15]. Thus, RWH implementation research could draw on existing frameworks and reporting requirements from other fields, to ensure that it is not underreported and under indexed, as alarmed by Rycroft-Malone & Burton [4].…”
Section: Discussionmentioning
confidence: 99%
“…One plausible explanation is that implementation strategies are difficult to evaluate and may coexist as a support to evidence-based interventions, making them an undesirable subject to address [11,12]. In conjunction to this, there is an absence of research evaluating RWH implementation strategies, despite previous research [13][14][15] revealed that they are poor. This indicates that research into fidelity by focusing on strategies is critical in RWH implementation.…”
Section: Intervention Fidelity and Implementation Fidelitymentioning
confidence: 99%
“…This reduced the burden of urban drains Buildings that are equipped with stormwater tanks are common practice in capturing stormwater. These are reported in the past studies, for example, Araujo et al [15] had anticipated the significance of the rainwater harvesting tank within a building; Lestari et al [16] had illustrated the benefits of having an underground tank in a school complex; Sharma and Gardner [17] maintained that building codes in Australian had increased the installation of stormwater tanks across Australian cities.…”
Section: Treesmentioning
confidence: 92%